2011
DOI: 10.1039/c1lc20524b
|View full text |Cite
|
Sign up to set email alerts
|

A digital microfluidic method for dried blood spot analysis

Abstract: Blood samples stored as dried blood spots (DBSs) are emerging as a useful sampling and storage vehicle for a wide range of applications. Unfortunately, the surging popularity of DBS samples has not yet been accompanied by an improvement in automated techniques for extraction and analysis. As a first step towards overcoming this challenge, we have developed a prototype microfluidic system for quantification of amino acids in dried blood spots, in which analytes are extracted, mixed with internal standards, deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
106
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 43 publications
0
106
0
Order By: Relevance
“…In method 2 (b), a 3.2-mm diameter punch from filter paper bearing dried blood is positioned on the device surface. (110) In the initial publication Jebrail et al demonstrated that there was no significant difference in data generated using DMF or conventional DBS extraction techniques to quantify analytes that are commonly measured as biomarkers for amino acid metabolism disorders in new-born patients. A collaboration between Abu-Rabie and Spooner (GSK), and the Institute for Biomaterials and Biomedical Engineering at the University of Toronto was established to further investigate this technique (66) .…”
Section: Digital Microfluidics (Dmf)mentioning
confidence: 99%
See 1 more Smart Citation
“…In method 2 (b), a 3.2-mm diameter punch from filter paper bearing dried blood is positioned on the device surface. (110) In the initial publication Jebrail et al demonstrated that there was no significant difference in data generated using DMF or conventional DBS extraction techniques to quantify analytes that are commonly measured as biomarkers for amino acid metabolism disorders in new-born patients. A collaboration between Abu-Rabie and Spooner (GSK), and the Institute for Biomaterials and Biomedical Engineering at the University of Toronto was established to further investigate this technique (66) .…”
Section: Digital Microfluidics (Dmf)mentioning
confidence: 99%
“…In 2011 Jebrail et al reported proof of concept for a fast and efficient digital microfluidic (DMF) method for dried blood spot analysis (110) . DMF is a fluid handling technique where discrete droplets of samples and regents are manipulated on an open surface by applying a series of electrical potentials to an array of electrodes.…”
Section: Digital Microfluidics (Dmf)mentioning
confidence: 99%
“…Microfluidics have been employed for alternative matrix collection and sample preparation in conjunction with tandem MS. One example includes the use of a lab-on-a-chip for sample preparation of either a DBS punch or a directly applied capillary blood droplet 144 …”
Section: Microfluidicsmentioning
confidence: 99%
“…These analytes were then sensitively quantified using mass spectrometry. Dried blood spots could also be analyzed using a similar technique, avoiding the issues of fouling and clogging that challenge channelbased microfluidic devices (Jebrail et al 2011).…”
Section: Divide and Conquer: Droplets For High-throughput Biologymentioning
confidence: 99%